2015
DOI: 10.1007/s00125-015-3723-4
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus antibodies show no association with pancreatic islet autoantibodies in children genetically predisposed to type 1 diabetes

Abstract: Aims/hypothesis Viral infections have long been considered potential triggers of beta cell autoimmunity and type 1 diabetes. Recent studies have suggested that influenza A virus might increase the risk of type 1 diabetes. The present study evaluates this risk association in prospectively observed children at the time when islet autoimmunity starts and autoantibodies are first detected. Methods IgG class antibodies to influenza A virus were analysed in 95 case children whose antibody screening test turned perma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In one study, influenza A antibodies were not associated with initiation of islet autoimmunity in children, but this study did not investigate pandemic influenza A (H1N1), included asymptomatic influenza infections and did not study clinical type 1 diabetes as outcome [33]. In theory, viral infections may affect the progression from islet autoimmunity to clinical diabetes in the small proportion of individuals who are positive for islet autoantibodies [34].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, influenza A antibodies were not associated with initiation of islet autoimmunity in children, but this study did not investigate pandemic influenza A (H1N1), included asymptomatic influenza infections and did not study clinical type 1 diabetes as outcome [33]. In theory, viral infections may affect the progression from islet autoimmunity to clinical diabetes in the small proportion of individuals who are positive for islet autoantibodies [34].…”
Section: Discussionmentioning
confidence: 99%
“…No association between gut virome and influenza virus infection, and islet cell autoimmunity development42 43…”
Section: Defining the Preclinical Disease Periodmentioning
confidence: 99%
“…Recently, it has been shown that the influenza virus infection does not impair the antiviral immune response in NOD mice [36]. Also, human studies showed no significant difference in the titers of anti-influenza viral antibodies between nonvaccinated, genetically predisposed children to T1D and control children [37]. Our study showed that in the case of P. yoelii 17XNL infection, the NOD mice are unable to mount an anti-parasite antibody response, which infers our previous hypothesis that a major mechanism of immune evasion by malaria parasites relies on suppression of B-cell function throughout induction of parasite-specific Foxp3 + Treg cells [38].…”
Section: Discussionmentioning
confidence: 99%